Hygiene Factor Gaps and Their Influence on Employee Performance of Commercial Banks in Nepal. - Rijal, Madhu (Journal of Kathmandu BernHardt College, 2025)
This study explores how hygiene factors salary, bonuses, and health care benefits affect employee performance in commercial banks operating in Kathmandu, Nepal, using Herzberg’s Two-Factor Theory as its foundation. Employing a descriptive and causal-comparative research design, the research assesses the role of financial rewards and welfare provisions in shaping employee motivation, satisfaction, and productivity within the banking industry. The results indicate that although salary is a fundamental element in meeting employees’ basic needs, performance-based incentives and benefits such as bonuses and health care contribute more significantly to maintaining motivation, improving performance, and minimizing turnover. The findings underline that while hygiene factors do not directly drive motivation, they are vital for reducing dissatisfaction and supporting organizational stability. The study further stresses the importance of implementing transparent and fair compensation practices that integrate both basic pay and performance-linked rewards. By addressing shortcomings in hygiene factors, banks can foster employee loyalty, create supportive work environments, and ensure sustainable organizational productivity. Overall, this research enriches the field of human resource management by offering context-specific evidence on how compensation and welfare strategies impact employee performance in Nepal’s competitive service-oriented banking sector.